Serum Neurofilament Light Chain: A Marker of Nervous System Damage in Myopathies - Saak, Annika; Benkert, Pascal; Akgün, Katja; Willemse, Eline; Kuhle, Jens; Ziemssen, Tjalf; Jackson, Sandra; Schaefer, Jochen (Frontiers in Neuroscience, 2021)
Purpose: Neurofilament light chain in serum (sNfL) has been suggested as a biomarker for the assessment of neuroaxonal damage. Since NfL are not expressed in muscle, elevated sNfL in patients with primary myopathies suggest additional nervous system involvement. To verify this hypothesis, we measured sNfL in a series of patients with myopathies. Methods: sNfL were determined in 62 patients with molecular proven primary myopathies in whom some nervous system involvement may be predicted: myotonic dystrophy type I and II (DM I, II) and mitochondrial disease. In addition, sNfL were measured in 8 patients with facioscapulohumeral muscular dystrophy (FSHD) and in a disease control group caused by genetic defects exclusively expressed in muscle. Results: sNfL values were significantly elevated in the DM I, the DM II and the mitochondrial group, with FSHD patients showing the lowest sNfL elevations. sNfL levels in the disease control group were not different from the healthy controls. A significant correlation between repeat length and sNfL levels was found in the DM I patients, but not in the DM II patients. Mitochondrial patients with encephalopathy showed significantly higher sNfL concentrations compared to patients with only muscular symptoms. Conclusions: sNfL levels are elevated in myopathies with, based on the underlying molecular defect or clinical features, established nervous system involvement, i.e. myotonic dystrophies and mitochondrial disorders. sNfL were also raised in FSHD, where involvement of the nervous system is not usually clinically apparent. Thus, sNfL concentrations may serve as a biomarker for additional neuronal damage in primary myopathies.